Summary measures for assessing the risk of a new disease: The case of the sexual transmission of HIV. - Declich, Silvia. (University of Ottawa (Canada), 1994)
The overall goal of this work is to critically assess and clarify methodologies for risk assessment and summary measure development which may be useful in appraising the risk involved in sexual transmission of HIV. The source of information for the available methods for risk assessment which various disciplines have developed, was a systematic review of the literature, the raw material being papers containing indexes assessing risk. Papers containing information about the development procedure were selected and sorted into reasonably homogeneous groups, which resulted in the proposal of a classification for risk assessment methods. The proposed classification identified the following methods: (1) the empirical method, which relies on collected data; (2) the judgemental method, which is based on the opinions of experts; (3) the psychometric method, which is built on a theoretical hypothesis about the construct; and (4) the mathematical method, which is based on an abstract representation in mathematical form of the phenomenon under study. A strategy similar to the one used in the search for risk assessment methods was employed in the search of the literature for existing indexes for the risk of HIV due to sexual behaviour. A logical progression of methods over time is evident, with the mathematical method as a foundation of risk assessment, followed by the psychometric method supported by a theoretical hypothesis, and finally, the judgemental and empirical methods, which require a sufficient amount of experts' knowledge and empirical data, respectively. The assessment of risk for HIV infection seems to be reaching the final stage of this progression. (Abstract shortened by UMI.)
Keywords: Psychology, Behavioral.